2022
DOI: 10.3390/ijms23063405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Applications of Bacterial Sporulation and Germination in the Intestine

Abstract: Recent studies have suggested a major role for endospore forming bacteria within the gut microbiota, not only as pathogens but also as commensal and beneficial members contributing to gut homeostasis. In this review the sporulation processes, spore properties, and germination processes will be explained within the scope of the human gut. Within the gut, spore-forming bacteria are known to interact with the host’s immune system, both in vegetative cell and spore form. Together with the resistant nature of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 230 publications
0
17
0
1
Order By: Relevance
“…Spores’ direct incorporation into animal feed, circumventing further protection processes, such as encapsulation, together with their simple production and long shelf-life without needing refrigeration ( 51 , 69 ), are also attractive characteristics from the industrial point of view ( 70 ). Adding to this “needle-free” and “refrigeration-free” potential, B. subtilis spores adjuvant properties ( 18 , 19 , 71 73 ) and contribution to GALT (gut associated lymphoid tissue) development ( 67 , 74 – 76 ), increases their potential as oral delivery systems of antigens. Previous reports have shown the application of B. subtilis spores as oral (or mucosal) vaccines in different animals, including aquatic animals ( 20 , 24 , 26 29 , 31 , 32 , 60 , 64 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spores’ direct incorporation into animal feed, circumventing further protection processes, such as encapsulation, together with their simple production and long shelf-life without needing refrigeration ( 51 , 69 ), are also attractive characteristics from the industrial point of view ( 70 ). Adding to this “needle-free” and “refrigeration-free” potential, B. subtilis spores adjuvant properties ( 18 , 19 , 71 73 ) and contribution to GALT (gut associated lymphoid tissue) development ( 67 , 74 – 76 ), increases their potential as oral delivery systems of antigens. Previous reports have shown the application of B. subtilis spores as oral (or mucosal) vaccines in different animals, including aquatic animals ( 20 , 24 , 26 29 , 31 , 32 , 60 , 64 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the phylum Bacillota (formerly Firmicutes) include many spore-forming lineages such as Bacillus and Clostridium . These spore-forming members are dominant in healthy gut microbiomes, with many strains within this group also considered common intestinal pathogens (2, 3). Sporulation is a complex form of dormancy, involving hundreds of genes, that helps these bacteria contend with spatial and temporal variation in environmental conditions in human guts and facilitate transmission (2, 4).…”
Section: Main Textmentioning
confidence: 99%
“…This finding is different than most examples of AMGs, where the phages control a metabolic process by phage-encoded enzymes, or by expression of modulators of host enzyme activity (5). It may be that phages manipulate host sporulation by interfering with the tightly regulated transcriptional program that is essential for this complex developmental process (2).…”
Section: Main Textmentioning
confidence: 99%
“…The exceptional longevity of the spore in the environment is the main reason for the ubiquitous distribution of these organisms in nature, found in soil, air, fermented foods, and the human gut [37,39]. The sporulation process starts with forming an asymmetrical septum that produces two different compartments: a bigger one called the mother cell and the forespore, the smaller one.…”
Section: Bacterial Spore Sporulation and Intestinal Life Cyclementioning
confidence: 99%
“…Then, germination-derived cells can sporulate in the lower part of the intestine, thus performing an entire life cycle in the animal GUT [39]. Several works have shown that many Bacillus species, including Bacillus clausii, Bacillus pumilus, Bacillus polyfermenticus, and B. subtilis contribute to the composition of GUT microbiota and so maintain host health by performing nutritional, immunological, and physiological functions [37,[40][41][42]. Spores administered by the intragastric route can transit through the stomach thanks to their extreme resistance.…”
Section: Bacterial Spore Sporulation and Intestinal Life Cyclementioning
confidence: 99%